Assessment and design of real world driving cycles targeted to the calibration of vehicles with electrified powertrain. (December 2021) - Doulgeris, Stylianos; Toumasatos, Zisimos; Prati, Maria Vittoria; Beatrice, Carlo; Samaras, Zissis
Vehicles' powertrain electrification is one of the key measures adopted by manufacturers in order to develop low emissions vehicles and reduce the CO2 emissions from passenger cars. High complexity of electrified powertrains increases the demand of cost-effective tools that can be used during the design of such powertrain architectures. Objective of the study is the proposal of a series of real-world velocity profiles that can be used during virtual design. To that aim, using three state of the art plug-in hybrid vehicles, a combined experimental, and simulation approach is followed to derive generic real-world cycles that can be used for the evaluation of the overall energy efficiency of electrified powertrains. The vehicles were tested under standard real driving emissions routes, real-world routes with reversed order (compared to a standard real driving emissions route) of urban, rural, motorway, and routes with high slope variation. To enhance the experimental activities, additional virtual mission profiles simulated using vehicle simulation models. Outcome of the study consists of specific driving cycles, designed based on standard real-world route, and a methodology for real-world data analysis and evaluation, along with the results from the assessment of the impact of different operational parameters on the total electrified powertrain.